ANALISIS MANAJEMEN PESERTA DIDIK PADA TAMAN KANAK-KANAK SE-KECAMATAN TAMPAN KOTA PEKANBARU - Anggun Putri Anggun Putri; Zulkifli N Zulkifli N '; Daviq Chairilsyah Daviq Chairilsyah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to determine the Pupil Personnel Management Activities in Kindergarten at Tampan District of Pekanbaru City. The population and sample of this research is all kindergarten principal totaling 50 people. Data collection techniques used were a questionnaire. Test data analysis techniques using ITEMAN Ver3.0 program, while research data analysis technique using a percentage formula. From the research results pupil personnel management in kindergarten overall obtained percentage of 74.88%, it is in good category. Meanwhile, if viewed from each indicator, planning pupil personnel applicant indicator get a percentage of 77.43% categorized as good, arrangement of the new pupil personnel indicator get a percentage of 73.88% were in either category, grouping learners indicator get a percentage of 81, 50% are in the very good category, recorded the presence of learners indicator get a percentage of 83.67% are in the very good category, indicators of fostering discipline pupil personnel get a percentage of 76.00% are in the good category, to set mutation/transfer pupil personnel indicator get a percentage of 67.60% are in the good category. To set graduation of pupil personnel indicator get a percentage of 80.80% are in the very good category and still one indicator need focused guidance that is to set up a special service program which gets a percentage of 55%, that is categorized enough.Key words: Managemen, Pupil Personnel